The stolen year : how COVID changed children's lives, and where we go now - Kamenetz, Anya, 1980- (PublicAffairs, 2022)
"An NPR education reporter shows how the last true social safety net-- the public school system--was decimated by the pandemic, and how years of short-sighted political decisions have failed to put our children first. School has long meant much more than an education in America. 30 million children depend on free school meals. Schools are, statistically, the safest physical places for children to be. They are the best chance many children have at finding basics like eye exams, safe housing, mental health counseling, or simply a caring adult. Flawed, inequitable, underfunded, and segregated, they remain the most important engine of social mobility and the crucible of our democracy. The cost of closing our schools for so long during COVID, made with good intentions, has not yet been fully reckoned with. In The Stolen Year, NPR education reporter Anya Kamenetz shows that the roots of our crisis run far deeper than COVID. She follows families across the country as they lived through the pandemic. But she also dives deep into the political history that brought us to this point: Why we have no childcare system to speak of, why subsidies for families were cut to the bone, how children became the group most likely to live in poverty, how we overpolice and separate families of color, and how we are content to let the unpaid and underpaid labor of women, especially women of color and immigrants, stand in for a void of public and collective concern for children. Kamenetz makes the case that 2020 wasn't a lost year--it was taken from our children, by years of neglect and bad faith. We have failed to put them first. The American Rescue Plan offers new tax benefits for families and new funding for schools. But if progress stops there, and we revert to cutting funding and laying off school staff, another crisis will surely come. The Stolen Year is a passionately argued and emotional story, but also a demand for recompense"--